2019
DOI: 10.24193/subbchem.2019.2.40
|View full text |Cite
|
Sign up to set email alerts
|

Solubility, ductility and resilience of a PMMA denture resin with graphene and silver nanoparticles addition

Abstract: PMMA denture base materials are used for several decades without significant improvements in their composition. The addition of different fillers has been proved to improve some of the acrylic resin's characteristics. Recent studies focused on enhancing PMMA properties using nanoparticles. In our study we assessed the effect of adding graphene and silver nanoparticles on the solubility, ductility and resilience of a commercial denture base acrylic resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Fractures in materials depend on heterogeneity, interfacial adhesion between the components of the materials, and the structure of the content. 9 It was observed that the nanoparticles were agglomerated in the SEM images obtained, and the increase in concentration increased the amount of agglomeration. It is thought that the resulting agglomeration affects the bond strength negatively, as reported in studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Fractures in materials depend on heterogeneity, interfacial adhesion between the components of the materials, and the structure of the content. 9 It was observed that the nanoparticles were agglomerated in the SEM images obtained, and the increase in concentration increased the amount of agglomeration. It is thought that the resulting agglomeration affects the bond strength negatively, as reported in studies.…”
Section: Discussionmentioning
confidence: 94%
“…[2][3][4][5]8 In recent years, graphene and its derivatives have been used to improve the mechanical and biological properties of polymers. 2,9,10 Graphene is a crystalline form of carbon. It has a honeycomb-like structure that increases the surface area.…”
mentioning
confidence: 99%
“…Other studies using graphene silver nanoparticles to improve PMMA's mechanical proprieties have shown that in a concentration of 1wt%, the nanoparticles have a beneficial effect on the resin's modulus of resilience but decrease the ductility. On the other hand, a 2wt% concentration improved resilience and reduced ductility [26].…”
Section: Discussionmentioning
confidence: 97%